Rumen Microbiome and Metabolome of High and Low Residual Feed Intake Angus Heifers - Liu, Yue; Wu, Hao; Chen, Wanbao; Liu, Chang; Meng, Qingxiang; Zhou, Zhenming (Frontiers in Veterinary Science, 2022)
Feed cost is the greatest expense during cattle production; therefore, reducing it is critical to increasing producer profits. In ruminants, the microbial population is important to nutrient digestion and absorption in the rumen. The objective of this study was to investigate the relationships among rumen bacteria, rumen metabolites, and the residual feed intake (RFI) phenotype of beef cattle. Twelve Angus heifers were selected to be sampled and divided into high RFI (HRFI; n = 6) group and low RFI (LRFI; n = 6) group according to their RFI classification determined during the feedlot-finishing period. After the ruminal liquid samples were collected at slaughter, Illumina MiSeq sequencing of the 16S rRNA V3-V4 region and liquid chromatography-mass spectrometry (LC-MS) were performed to determine their bacterial composition and metabolites, respectively. At the phylum level, the relative abundance of Proteobacteria was higher in the LRFI group than in the HRFI group (P < 0.01). At the family level, the relative abundances of Rikenellaceae (P < 0.01), Ruminococcaceae, Bacteroidales_S24-7_group, and Lachnospiraceae (P < 0.05) were significantly higher in the LRFI group. At the genus level, the relative abundances of Rikenellaceae_RC9_gut_group and Ruminiclostridium_1 were higher in the LRFI group (P < 0.01), as were the relative abundances of norank_f__Bacteroidales_S24-7_group, Lachnospiraceae_ND3007_group, and Lachnospiraceae_NK3A20_group (P < 0.05). Moreover, the genera Rikenellaceae_RC9_gut_group, Ruminococcaceae_NK4A214_group, Christensenellaceae_R-7_group, Ruminococcaceae_UCG-010, Lachnospiraceae_ND3007_group, Ruminiclostridium_1, and Lachnospiraceae_NK3A20_group were negatively associated with the RFI; both foundational and keystone species are associated with feed efficiency phenotype. In addition, rumen metabolomics analysis revealed that the RFI was associated with significantly altered concentrations of rumen metabolites involved in protein digestion and absorption, Linoleic acid metabolism, Lysine degradation, and Fatty acid degradation. Correlation analysis revealed the potential relationships between the significantly differential ruminal metabolites and the genera ruminal bacteria. The present study provides a better understanding of rumen bacteria and metabolites of beef cattle with different RFI phenotypes and the relationships among them, which are potentially important for the improvement of beef cattle feed efficiency.